Co-ops 2.0: Alternative Retail Strategies to Support a Sustainable Transition in Food Retailing - Schulze, Maureen; Spiller, Achim; Risius, Antje (Frontiers in Sustainability, 2021)
While modern food retailing is characterized by high price pressure and low-quality differentiation resulting in a limited supply of sustainably produced alternative food products, cooperative retailing structures offer additional synergies in terms of logistics and operations that hold great potential to support the expansion of sustainable produce. Many retailers in Germany are organized in cooperatives of sufficient size to generate large-scale effects while still allowing individual retailers to pursue independent business structures. Cooperatives targeted to elaborate on collectivity operate a business. In economic terms this means that scale effects are used to elaborate and help single business. In the food sector cooperative structures in Germany provide a substantial impact in food delivery and provision, especially fresh foods are very sensitive and need fast circulation. In regard to sourcing sustainable, local and regional foods are often produced (or rather crafted) in small scale entities. This paper asks the question of how and whether cooperative marketing structures help to deliver and use scale effects of larger entities, while still collaboratively encouraging food marketing. Accordingly, this paper reports on an investigation of the main challenges faced by members of a large-scale cooperative in retailing sustainably produced products and the motives of these retailers in choosing whether or not to sell such products. Taking the case of grass-fed beef sold by retailers within a large German cooperative, the study reveals that some of the obstacles to selling this sustainable product are comparable to challenges typically encountered in other retailing channels beyond cooperative structures. However, we also find that the flexibility of the cooperative structure enables individual retailers to bring their intrinsic motivation into (sustainable) action in the marketplace while taking advantage of the support offered by the cooperative in terms of marketing and consultation, etc. This analysis confirms that personal motivation within this cooperative structure is a strong determinant for individual retailers to pursue different pathways for the marketing and sale of sustainably produced food.